Supportive supervision to improve service delivery in low-income countries: is there a conceptual problem or a strategy problem? - Avortri, Gertrude Sika (BMJ Glob Health, 2019)
Supportive supervision is perceived as an intervention that strengthens the health system, enables health workers to offer quality services and improve performance. Unfortunately, numerous studies show that supervisory mechanisms in many low-income countries (LICs) are suboptimal. Further, the understanding of the concept and its implementation is still shrouded in misinterpretations and inconsistencies. This analysis contributes to a deeper understanding of the concept of supportive supervision and how reorganisation of the approach can contribute to improved performance. The effectiveness of supportive supervision is mixed, with some studies noting that evidence on its role, especially in LICs is inconclusive. Quality of care is a core component of universal health coverage which, accentuates the need for supportive supervision. In the context of LICs, it is imperative for supportive supervision to be implemented as an on-going approach. Factors that affect supportive supervision encompass cultural, social, organizational and context dimensions but the capacity of majority of LIC to address these is limited. To this end, we underscore the need to review the supportive supervision approach to improve its effectiveness, and ensure that facility-based supervision embodies as many of the envisioned qualities as possible. We thus make a case for a stronger focus on internal supportive supervision where internal refers to health facility/unit/ward level. Inherent in the approach is what we refer to as ‘supervisee initiated supportive supervision’. The success of this approach must be anchored on a strong system for monitoring, data and information management at the health facility level.